2013
DOI: 10.1007/s11274-013-1539-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of octanal on the mycelial growth of Penicillium italicum and P. digitatum

Abstract: The present study investigated the antifungal activity of octanal against Penicillium italicum and P. digitatum. Results showed that octanal exhibited strong antifungal activity against the test pathogens in a dose-dependent manner. Scanning electron microscopy observation revealed that octanal obviously altered the morphology of P. italicum and P. digitatum hyphae by causing the loss of cytoplasm and distortion of mycelia. A rapid increase in the membrane permeability of P. italicum and P. digitatum was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…DEM (6.25 µg mL −1 ) cause heavy damage to mycelium plasma membrane of P. italicum , leading to spillage of intracellular macromolecular cytoplasmic components into the extracellular suspensions through damaged sites. These findings indicated that DEM can induce damage to the mycelium plasma membrane of P. italicum and is mimicking the reports for various other antifungal agents like citral, octanal, and pinocembrin that kills P. italicum and reduces blue mold in citrus fruits [8,9,11,36]. Many related studies stated that P. digitatum induced green molds in citrus fruits and were also reduced in similar mechanisms by using α-terpineol, β-carbolines, citral, octanal, and citronellal [26,30,31,37].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…DEM (6.25 µg mL −1 ) cause heavy damage to mycelium plasma membrane of P. italicum , leading to spillage of intracellular macromolecular cytoplasmic components into the extracellular suspensions through damaged sites. These findings indicated that DEM can induce damage to the mycelium plasma membrane of P. italicum and is mimicking the reports for various other antifungal agents like citral, octanal, and pinocembrin that kills P. italicum and reduces blue mold in citrus fruits [8,9,11,36]. Many related studies stated that P. digitatum induced green molds in citrus fruits and were also reduced in similar mechanisms by using α-terpineol, β-carbolines, citral, octanal, and citronellal [26,30,31,37].…”
Section: Discussionsupporting
confidence: 67%
“…A similar study reported about 90% MGI against Alternaria solani in tomatoes, Cercospora arachidicola in peanuts, Physalospora piricola in apples, and Cladosporium cucumerium in cucumbers when treated with DEM at 50 µg mL −1 [35]. The DEM showed the lowest MIC value against P. italicum in comparation with pinocembrin (400 µg mL −1 ), octanal (64.11 µg mL −1 ), and citral (76.12 µg mL −1 ) in previous studies [8,9,11]. DEM treatment (6.25 µg mL −1 ) significantly reduced the spore germination (4.37%) of P. italicum brought lower than 5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SEM examinations could reveal that rough surface and shrinkage of cells were apparent in the treated hyphae (Tao et al 2014). SEM observations also confirmed the damage that the treated hypha demonstrated bending, entwining, shriveling, collapse and disorganization, and the breakage of the hypha was clearly visible (Jiang et al 2015).…”
Section: Discussionsupporting
confidence: 54%